Genetics of Human Longevity From Incomplete Data: New Findings From the Long Life Family Study. (21st March 2018) - Yashin, Anatoliy I; Arbeev, Konstantin G; Wu, Deqing; Arbeeva, Liubov S; Bagley, Olivia; Stallard, Eric; Kulminski, Alexander M; Akushevich, Igor; Fang, Fang; Wojczynski, Mary K; Christensen, Kaare; Newman, Anne B; et al.
Abstract: The special design of the Long Life Family Study provides a unique opportunity to investigate the genetics of human longevity by analyzing data on exceptional lifespans in families. In this article, we performed two series of genome wide association studies of human longevity which differed with respect to whether missing lifespan data were predicted or not predicted. We showed that the use of predicted lifespan is most beneficial when the follow-up period is relatively short. In addition to detection of strong associations of SNPs in APOE, TOMM40, NECTIN2, and APOC1 genes with longevity, we also detected a strong new association with longevity of rs1927465, located between the CYP26A1 and MYOF genes on chromosome 10. The association was confirmed using data from the Health and Retirement Study. We discuss the biological relevance of the detected SNPs to human longevity.